Discographies : dance music, culture, and the politics of sound - Gilbert, Jeremy, 1971- (Routledge, 1999)
Experiencing disco, hip hop, house, techno, drum 'n' bass and garage, Discographies plots a course through the transatlantic dance scene of the last last twenty-five years. It discusses the problems posed by contemporary dance culture of both academic and cultural study and finds these origins in the history of opposition to music as a source of sensory pleasure. Discussing such issues as technology, club space. drugs, the musical body, gender, sexuality and pleasure, Discographies explores the ecstatic experiences at the heart of contemporary dance culture. It suggests why politicians and agencies as diverse as the independent music press and public broadcasting should be so hostile to this cultural phenomenon.